The Population Pharmacokinetics of Rifampicin in Japanese Pulmonary Tuberculosis Patients - Nishimura, Takahiro; Kohno, Haruichi; Nagai, Hideaki; Maruoka, Daisuke; Koike, Yuichi; Kobayashi, Masahiro; Atsuda, Koichiro (Drug Research, 2020)
In Japan, tuberculosis has been recognized as one of the major infections requiring urgent measures because of its high morbidity rate even now especially in elderly people suffering from tuberculosis during the past epidemic and its reactivation. Hence, many Japanese clinicians have made efforts to suppress the onset of tuberculosis and treat it effectively. The objectives of this study are to (1) identify covariate(s) that may explain the variation of rifampicin, which is the key antitubercular agent, under the steady-state by evaluating its population pharmacokinetics and (2) to propose an appropriate dosing method of rifampicin to Japanese patients. For this purpose, serum concentration–time data were obtained from 138 patients receiving rifampicin (300–450 mg) and isoniazid (300–400 mg) every day over 14 days, and analyzed using nonlinear mixed effects model. Thereby, population pharmacokinetic parameters were estimated followed by elucidating relations between the parameters and statistical factors. The analysis adopted one-compartment model including Lag-time by assuming that the absorption process is 0+1st order. The analyses demonstrate that meal affected the bioavailability, primary absorption rate constant, and zero order absorption time in the constructed model. A body weight calculated from the power model was selected as the covariate by the Stepwise Covariate Model method and found to highly affect the clearance in the range from −31.6% to 47.4%. We conclude that the dose in Japanese tuberculous patients can be well estimated by the power model formula and should be taken into consideration when rifampicin is administered.
Keywords: population pharmacokinetics; rifampicin; Japanese tuberculosis patients